2010
DOI: 10.1007/s12231-010-9123-2
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Traditional Knowledge, Use Value, and the Contribution of Tamarind (Tamarindus indica L.) to Rural Households’ Cash Income in Benin

Abstract: Women's Traditional Knowledge, Use Value, and the Contribution of Tamarind (Tamarindus indica L.) to Rural Households' Cash Income in Benin. This study examined differences in knowledge, use values, and contribution of tamarind (Tamarindus indica) to women's cash income during the dry season, focusing on seven tribal groups in Benin. Data were gathered using semistructured individual interviews and monitoring, and were analyzed using quantitative ethnobotanical methods. Principal component analysis was applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
63
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 21 publications
12
63
1
8
Order By: Relevance
“…Overall, we found significant ethnic variation in knowledge and utilization of L. lanceolata, as it has been found for several multipurpose use tree species in Benin: Parkia biglobosa (Koura et al, 2011), Tamarindus indica (Fandohan et al, 2010), Adansonia digitata (Assogbadjo et al, 2008) and Caesalpinia bonduc . Our results confirmed difference of knowledge between age classes and gender in medicinal plants utilization previously observed (Müller-Schwarze, 2006;Camou-Guerrero et al, 2008).…”
Section: Discussionsupporting
confidence: 54%
“…Overall, we found significant ethnic variation in knowledge and utilization of L. lanceolata, as it has been found for several multipurpose use tree species in Benin: Parkia biglobosa (Koura et al, 2011), Tamarindus indica (Fandohan et al, 2010), Adansonia digitata (Assogbadjo et al, 2008) and Caesalpinia bonduc . Our results confirmed difference of knowledge between age classes and gender in medicinal plants utilization previously observed (Müller-Schwarze, 2006;Camou-Guerrero et al, 2008).…”
Section: Discussionsupporting
confidence: 54%
“…The high ethnic diversity in South Borgou may also explain the highest record of antidiabetic plants. In this line, some past studies have well documented the positive association of Idatcha, Mahi, and Fulani people (interviewed in South Borgou) with the use of plant species (Assogbadjo et al 2010, Fandohan et al 2010, Gaoué & Ticktin 2009, Koura et al 2011). …”
Section: Location-related Knowledge and Interaction Between Location mentioning
confidence: 89%
“…We explored different phytogeographical districts that spread over the three bioclimatic regions, from southern to northern Benin. The country is a prime study area in that traditional medicine is widespread and still the mainstay of primary health care of many people (Assogbadjo et al 2010, Fandohan et al 2010, Koura et al 2011). However, very few studies have investigated the use of antidiabetic plants in Benin (Fah et al 2013).…”
Section: Ethnobotany Research and Applications 232mentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding indigenous knowledge of exploiting and managing local natural resources is recognized as crucial for the development of management strategies for the sustainable use of those resources (Fandohan et al 2010). Ethnobotanical studies have shown that indigenous knowledge is important for the conservation of biological and cultural diversity as well as for the sustainable use of these resources (Luoga et al 2000).…”
Section: Introductionmentioning
confidence: 99%